FACTORS INFLUENCING SPONSORSHIP MANAGEMENT IN PROFESSIONAL FOOTBALL LEAGUES OF THAILAND - Untarabutr, Nutnatee; Jarernsiripornkul, Sakchai (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2022)
This research paper presents the factors that influence the management of sponsorships in the professional football league of Thailand. The research collected insights from semi-structured interviews with thirteen business organizations and four professional football clubs competing in the Thai football leagues to examine the factors influencing sponsorship management in the football leagues in Thailand. The research shows the factors that influence sponsorship management in professional football leagues in Thailand in three sections: sponsorship objectives, sponsorship decision-making, and evaluation of the effectiveness of sponsorship management in the Thai football leagues. The research also conducted documentary research related to sponsorship management in the Thai Football League to analyze the factors influencing sponsorship management in the Thai football League. The research work was analyzed using data triangulation and method triangulation to analyze the data to ensure reliability and accuracy. Research has shown that sponsorship objectives focus on creating a corporate image, building public view, and executive interest, where the sponsor and the sponsee (A person or organization associated with the sport to find capital, foods, accommodations, sports articles of clothing, rental of training facilities, sports-related resources, sports equipment for running a sports event. [01]) have the utmost importance. Creating visibility and giving opportunities to give back to society is of secondary importance. The decision-making of sports sponsorship is an essential part of the sponsorship management of the professional football league of Thailand. The research found that the views gained by sponsors and sponsees focus on the expense of the sponsorship. The image and status regarding the potential sponsored party are the first two factors influencing sponsorship decisions in Thai football. The revenue chance for the organization, the presentation to the organization’s target market, and the capacity to develop the organization’s image is a minor criterion for sponsoring decisions in the Thai football league. The research summary shows that the Thai league has not yet been planning to evaluate sponsorship effectiveness based on data obtained from the perspective of the sponsor and sponsee.